Wireless Sensor Network Design for Earthquake’s and Landslide’s Early Warnings - Haziel Latupapua; Andrias Izaac Latupapua; Abdi Wahab; Mudrik Alaydrus (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Indonesia including the earthquake-prone areas because Indonesia is situated between three tectonic plates and in the Maluku island it self has a fault line 10 zones, the impact of frequent tectonic earthquake on the island of Maluku resulted in a domino effect, such as the frequent occurrence of soil landslides at several points in the city of Ambon, and due to faults that occur lead ease rising sea levels to population centers so Ambon was becoming flooded. This research aims to design and analyzing measurements of earthquake monitoring system indication and landslides integrated via Wireless Sensor Network (WSN) by implementing a star topology, technology, ZigBee, WiFi technology Shield and GPRS (General Packet Radio Service). Researchers technology utilizes Wireless Sensor Network (WSN) to acquire and distribute widely the data to be monitored and controlled centrally.By detecting suspicious indicators such as tremor or landslides through nodes or end devices, the system provides information to the number of monitors and warnings. The system can also be accessed in real-time via the website by accessing the IP address of the Wireless-LAN devices Wi-Fi Arduino Shield.